Validation of paliperidone in pharmaceutical dosage Form by reverse phase high performance Liquid chromatography - RAJAN V. RELE (International Journal of Pharma and Bio Sciences, 2017)
Paliperidone is Chemically, (±)-3-[2-[4-(6-fluoro-1,2benzisoxazol-3-yl)-1-piperidinyl]ethyl]-6,7,8,9-tetrahydro-9-hydroxy-2-methyl-4H-pyrido[1,2- a]pyrimidin-4-one It is a psychotropic agent belongs to the chemical class of benzisoxazole derivatives. A validation method was developed for paliperidone by using reverse phase liquid chromatography. For separation column was used as Water symmetry RP 8 The mobile phase made of buffer and acetonitrile (65:35 % v/v). A 238 nm wavelength was selected for chromatographic study. The ICH guidelines were used for robustness and stability study. The method has been successfully used to assay of pharmaceutical dosage form i.e. tablets with good recoveries.